THE DEVELOPMENT OF PREZI APPLICATION-BASED LEARNING MEDIA ON ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SMP MUHAMMADIYAH 02 MEDAN - Wahiddin Wahiddin; Mesiono Mesiono; Haidir Haidir (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The objective of this study is to provide realistic, practical, and effective Prezi application-based learning media in PAI subjects in order to improve students' comprehension ability. This is a development study using the ADDIE development model. The research participants were 15 students from VIII-1 and 15 students from VIII-2. The study's findings revealed that the validity of the learning media generated was assessed based on the validity of the learning media by the validators, with a total average value of 3.73 ("Valid" category). Meanwhile, the observation score of learning implementation in trial II, which was 3.73, demonstrated the usefulness of learning media (well-implemented category). In addition to the effectiveness of learning media in four aspects, namely classical completeness of 86.67% (13 students), student activity observation scores in trial II for three meetings were 22.2%, 26.87%, 26.87%, 13, 9%, 7.87%, and 2.32%, observation of the teacher's ability to manage learning was 3.79 (the "Good" category), teacher's response was 3.78 (the "Interested" category), and student's response was 3.74 ("Interested" category). According to the normalized gain index, there was an increase in value in trial II with a score of 0.40. (the "moderate" criteria).